Cumulative Roles for Epstein-Barr Virus, Human Endogenous Retroviruses, and Human Herpes Virus-6 in Driving an Inflammatory Cascade Underlying MS Pathogenesis - Meier, Ute-Christiane; Cipian, Richard Christopher; Karimi, Abbas; Ramasamy, Ranjan; Middeldorp, Jaap Michiel (Frontiers in Immunology, 2021)
Roles for viral infections and aberrant immune responses in driving localized neuroinflammation and neurodegeneration in multiple sclerosis (MS) are the focus of intense research. Epstein-Barr virus (EBV), as a persistent reactivating virus with major immunogenic influences, is considered to be the primary initiating factor in MS, triggering localized inflammation in the central nervous system (CNS). This triggering may occur directly via viral products (RNA and protein) or indirectly via antigenic mimicry involving B-cells, T-cells and cytokine-activated astrocytes and microglia cells damaging the myelin sheath of neurons. A central role is proposed for persistent secretion of inflammatory EBER1 and LMP1 containing exosomes and repetitive release of EBNA1-DNA complexes by apoptotic EBV+ B-cells. This may be accompanied by cytokine or EBV-induced expression of human endogenous retrovirus-W (HERV-W) elements and possibly by activation of human herpesvirus-6 (HHV-6) in early-stage CNS lesions, each contributing to an inflammatory cascade causing the relapsing-remitting neuro-inflammatory and/or progressive features characteristic of MS. Elimination of EBV-carrying B-cells by antibody- and EBV-specific T-cell therapy may hold the promise of reducing EBV activity in the CNS, thereby limiting CNS inflammation, MS symptoms and possibly reversing disease. Other approaches targeting HHV-6 and HERV-W and limiting inflammatory kinase-signaling to treat MS are also being tested with promising results. This article presents an overview of the evidence that EBV, HHV-6, and HERV-W may have a pathogenic role in initiating and promoting MS and possible approaches to mitigate development of the disease.